1996
DOI: 10.1111/j.1399-6576.1996.tb05573.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural vs. intravenous infusion of alfentanil in the management of postoperative pain following laparotomies*

Abstract: Compared to intravenous infusion of alfentanil epidural infusion resulting in the same plasma concentrations is not more effective in relieving postoperative pain. In view of this observation we were not able to demonstrate a spinal mechanism of alfentanil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Since the current practice in the UK is to use postoperative regimens with insufficiently high concentrations of opioids to elicit spinal analgesia, the full potential of epidural opioids is not being realised. There is plenty of evidence showing that higher concentrations produce segmental analgesia and that these can be used clinically [11–24], and this evidence should be utilised and built upon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the current practice in the UK is to use postoperative regimens with insufficiently high concentrations of opioids to elicit spinal analgesia, the full potential of epidural opioids is not being realised. There is plenty of evidence showing that higher concentrations produce segmental analgesia and that these can be used clinically [11–24], and this evidence should be utilised and built upon.…”
Section: Resultsmentioning
confidence: 99%
“… that fentanyl has an equivalent potency when given epidurally and i.v. [11–22]; that there are equal plasma drug levels for epidural and i.v. analgesic regimens of equal potency [13–15, 17–23]; that there is a non‐segmental analgesic effect after the epidural administration of the drug [24].…”
Section: The Site Of Action Of Epidural Opioids – a Review Of The Evimentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain is undertreated for varied reasons viz., lack of knowledge regarding effective dose ranges, duration of action of opioids and unfounded fear of respiratory depression and addiction. However, strong opioids viz., morphine,[ 1 ] fentanyl,[ 2 ] alfentanyl,[ 3 ] etc., have always been the gold standard in the management of postoperative pain. The major hindrance to the liberal use of strong opioids in the postoperative zone is the threat of respiratory depression[ 4 ] especially in children where the optimal dose for effective pain control is higher than in adults because of a larger volume of distribution[ 5 ] posing a relatively narrow margin of safety.…”
Section: Discussionmentioning
confidence: 99%
“…Van den Nieuwenhuyzen et al. reported that epidural and intravenous infusions of alfentanil resulted in equivalent, subanalgesic, plasma concentrations and in similar postoperative morphine consumption (25). Also, they were unable to demonstrate a spinal mechanism of action of epidurally administered alfentanil.…”
Section: Discussionmentioning
confidence: 99%